Особенности оценки радоноопасности Сухачёвского хвостохранилища радиоактивных отходов - Солодовникова, Лидия Николаевна; Тарасов, Владимир Алексеевич (НТУ "ХПИ", 2017)
В работе представлены результаты высокоточного радонового мониторинга 2-й секции Сухачёвского хвостохранилища радиоактивных отходов Производственного объединения «Приднепровский химический завод». Проведена оценка возможностей превышения значений объёмной активности радона-222 в воздухе вокруг хвостохранилища. Также проведена оценка радоноопасности территории хвостохранилища по плотности потока радона-222 с его поверхности. На основании проведенных оценок подтверждена радоноопасность обследованных территорий. Показано, что поток радона-222 с поверхности хвостохранилища можно уменьшить, используя современные технологии изоляции и рекультивации хвостохранилищ. Рассмотрена возможность дальнейшего использования свободного объема хвостохранилища с учетом радиационной составляющей сбрасываемых отходов.

The results of high-precision radon monitoring of the 2nd section of the Sukhachevsky tailings dump of the Pridneprovsky Chemical Plant production association are presented. The radon hazard assessment of the 2nd section of the Sukhachevsky tailings dump of radioactive waste was carried out by measuring the equivalent equilibrium volumetric activity (EROA) of radon-222 in the air around the tailing site and the flux density (exhalation) of radon-222 from the surface of the tailing site.The possibility of exceeding the values of volumetric activity of radon-222 in the air around the tailing dump was assessed. The radon hazard of the tailing site was estimated from the radon-222 flux density from its surface, since its values were significantly higher than the allowable values. The radon hazard of the surveyed territories was confirmed based on the conducted assessments. It is shown that the flux of radon-222 from the surface of the tailings can be reduced using modern technologies of isolation and reclamation of tailing dumps such as tailing dumps with «WISMUT» technology and non-reactive industrial wastes. The possibility of further use of the tailing dump free volume taking into account the radiactive component of the discharged waste is considered.
The peculiarities of assessing the radon hazard of the Sukhachev tailing dump of radioactive wastes
Keywords: мониторинг; безопасность экологическая; газ радиоактивный; radon hazard; high-precision monitoring; tailing dump; radioactive waste